2004
DOI: 10.1111/j.1464-5491.2004.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood diabetes: parents’ experience of home management and the first year following diagnosis

Abstract: The experience of parents in this study suggests that parents of children with newly diagnosed diabetes are able to cope successfully when given the opportunity to start treatment at home. Therefore, if children with diabetes are clinically well at diagnosis, this study supports home management as a system of care from the parents' point of view. These findings are relevant to clinicians, policy makers and health service managers involved in planning and providing paediatric diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
2
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 27 publications
(35 reference statements)
7
92
2
17
Order By: Relevance
“…Consistent with the findings of other studies [4,6,13,16,[21][22][23], we observed that worries about hypoglycaemia were a major concern for parents. Furthermore, in line with the speculations of other authors [7], we found that parents do increase their child's blood glucose levels to mitigate risk of hypoglycaemia.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Consistent with the findings of other studies [4,6,13,16,[21][22][23], we observed that worries about hypoglycaemia were a major concern for parents. Furthermore, in line with the speculations of other authors [7], we found that parents do increase their child's blood glucose levels to mitigate risk of hypoglycaemia.…”
Section: Discussionsupporting
confidence: 95%
“…As parents' accounts have demonstrated, and others have also shown [13][14][15], managing a child's diabetes is extremely complicated and difficult, requiring what Sullivan-Bolyai has termed 'constant vigilance' [16] and also entailing remote management strategies, as our findings have served to highlight. Despite their efforts to manage their child's diabetes both directly and remotely, parents in the present study described many situations and contexts which, from their perspectives, had an impact on their child's blood glucose control, but over which they could exercise little or no control.…”
Section: Discussionmentioning
confidence: 67%
“…Finally, environmental changes and changes to scheduling of clinics (where possible) to support friends and family attending would be useful, possibly including a monthly weekend, or evening, clinic, or even delivering some sessions in the home environment. 18 In conclusion, the results from this exploratory study have provided a preliminary insight into children's perceptions of how others in their social environment are affected by their diabetes. The implications of the current research demonstrate that it is clearly important for clinicians to consider not only children's adjustment to their diabetes, but also the impact on their family environment.…”
Section: Original Articlementioning
confidence: 82%
“…Most qualitative research exploring patients' and carers' views and experiences use interviews or focus groups as data collection methods (e.g. Alazri, Heywood, Neal, & Leese, 2007;Kendall et al, 2009;Lowes, Lyne, & Gregory, 2004;Naithani, Gulliford, & Morgan, 2006;Stenner, Courtenay, & Carey, 2011). Patients' accounts can identify aspects of care they value and those they perceive as unhelpful.…”
Section: Patient and Carer Perspectives Of Health Carementioning
confidence: 98%